Comprehension and production of narrative macrostructure in Swedish: A longitudinal study from age 4 to 7. Issue 4 (August 2019) - Lindgren, Josefin
This article reports results from a longitudinal study from age 4 to 7 of comprehension and production of narrative macrostructure in Swedish monolingual children ( N = 17). Baby Birds / Baby Goats from the Multilingual Assessment Instrument for Narratives (LITMUS-MAIN) were used to elicit narratives and ask comprehension questions at age 4;4, 5;10 and 7;4. Results showed a steep development from age 4;4 to 5;10 in both comprehension and production of macrostructure, but only some further development in comprehension to age 7;4. For the measures studied, children seem to reach a plateau around age 6. Consistent differences between comprehension and production (higher scores in comprehension) and between stories (higher scores on Baby Goats ) were found across time points.